International courts and domestic politics - Wind, Marlene, 1963- (Cambridge University Press, 2018)
"Most studies describing this evolution have either drawn on classical legalistic approaches (see e.g. Aust and Nolte 2016; Keller and Stone Sweet 2008 or Mackenzie, Romano and Shany 2010) or been developed by constitutionalists?often from political science and sociology?preoccupied with mapping the global development and influence of ICs (see e.g. Slaughter 2000; Slaughter 2004; Slaughter and Burke-White 2006; Romano, Alter and Shany 2013 and Alter 2014). While the more classical legal scholarship has been predominated by accounts that outline principles and application of IC case law in national courts, constitutionalists have focused on actual practice, describing the evolution and functioning of ICs more broadly. What has unified both strands of research, however, is the often implicit description of a universal and unidirectional strengthening of legalization and judicialization in global affairs. The present volume puts the question in a different way. We do not from the outset normatively assume that ICs are important and powerful actors or that national actors without further ado cite, embrace or enter into a constructive dialogue with these supranational bodies. Rather what this book does is to ask?from a multidisciplinary perspective?how and to what degree do ICs actually influence, impose constraints on and create loyalty from those actors involved? It is our claim that rather little research has been occupied with the actual effects on the ground for those national courts, political institutions and citizens who are formally governed by the increased judicialization"-- Provided by publisher
Keywords: International courts.; International and municipal law.; International law and human rights.; Tribunaux internationaux.; Droit international et droit interne.; Droit international et droits de l'homme.; LAW -- International.; International and municipal law; International courts; International law and human rights; National courts.; International law and national law.; Judicial dialogue.; Politics.; Electronic book.